A quest for waste reduction at institutions of higher learning: Investigating the integration of Six Sigma and Lean Six Sigma methodologies with total quality management - Brits, H.J. (South African Journal of Higher Education, 2020)
Abstract Institutions of higher learning are required to rethink strategies to eliminate ‘institutional waste’. The sector is facing numerous challenges with resource restrictions. Factors such as the impact of the Fees-must-fall campaign in South Africa and the global tendency of government initiatives to increase student enrolment targets, while subsidies, on a continual basis, are on the decrease, places institutions in higher education under enormous financial distress. This article argues that the majority of institutions’ quality management systems in South Africa and abroad are underpinned by the principles of Total Quality Management (TQM). There is a dearth of research on the implementation of Six Sigma and Lean Six Sigma in higher education. This article investigates the integration of Six Sigma and Lean Six Sigma as mechanisms to reduce waste in the higher education sector. It reflects on how this integration can enhance a university’s core business and institutional functions through processes of continuous quality assurance, the latter is characteristic of the principles of TQM.